Penerapan Proses Pengendalian dan Penjaminan Mutu di PT. XYZ - Sugiarto, Emaria; Edhiargo Toyosito, Rakay; Meliana, Fitri (JOURNAL INFORMATION TECHNOLOGY ENGINEERING AND SCIENCE, 2021)
The increase along with the development of the industrial world, the company requires preparation in terms of Quality Control which is supported by using equipment that can guarantee the quality of its products. Along with the development of technology, so many equipment in the form of sophisticated machines that can be used in carrying out the Quality Control process. Such equipment, for example, is a Contour Record machine, CMM, Microscope, Rondcom, and others. Therefore, to know that the Quality Control management in the Quality Assurance Department is running quite well, which in the process has used sophisticated supporting tools and adequate human resources capabilities. Based on the results obtained that the guarantee and control process at PT. Denso Indonesia is based on the standard operating process (SOP).